METHYL JASMONATE: NEW INSIGHTS INTO A POTENT PHYTOHORMONE - MR. GUNJEGAONKAR SHIVSHANKAR M; MR. T. S. SHANMUGARAJAN (International Journal of Pharma and Bio Sciences, 2016)
Current review is being prepared considering latest significant potential of plant stress hormone Methyl Jasmonate for its anticancer, anti-inflammatory and nociceptive actions. Plant stress hormones induces defense-related mechanisms in plants has been shown to be active against various cancer cells both in vitro and in vivo, without affecting normal cells. Anti-inflammatory activity of methyl Jasmonate derivatives shows significant protection against experimentally induced inflammation in animals. Study reveals that methyl Jasmonate modulated the pain mediators and shows significant Anti nociceptive actions against chemically and mechanically produced pain. Current review reveals various anticancer activities with methyl Jasmonate mode of actions in concise way.